CAD hijacks STING to impair antitumor immunity and radiotherapy efficacy of colorectal cancer - Zhengkun Cai; Zeyuan Cheng; Lu Zhang; Yuhan Zhang; Jinming Shi; Jing Jin; Zeyun Mi; Zhiyong Yuan; Zhiqiang Wu (Cell Death and Disease)
Abstract Radiotherapy (RT)-elicited antitumor immunity serves as a pivotal mechanism in RT-mediated tumor control. The strategic integration of RT with immunotherapies, particularly immune checkpoint blockade (ICB), is revolutionizing cancer therapeutics, demonstrating remarkable clinical potential. In this context, identifying molecular targets to potentiate radioimmunotherapy (RIT) efficacy represents a critical research priority. Emerging as a central immunomodulatory axis, the cGAS/STING signaling pathway bridges DNA damage response with antitumor immunity, positioning itself as a prime therapeutic target for radiation sensitization. Our study unveils caspase-activated DNase (CAD) as a previously unrecognized suppressor of cGAS/STING signaling that governs radiosensitivity in colorectal cancer (CRC). CAD physically blocks STING dimerization and cGAMP binding through a nuclease-independent function, thereby compromising RT-induced STING activation and subsequent type I interferon (IFN-I) production. Functional analyses demonstrated that CAD ablation potentiates CD8+ T cell infiltration/activation within the tumor microenvironment and synergizes with anti-PD-1 immunotherapy upon radiation. Translational validation revealed clinical correlations between CAD overexpression in CRC specimens and suboptimal radiotherapy responses coupled with diminished intratumoral CD8+ T cell infiltration. Collectively, our findings establish CAD as a novel rheostat of cGAS-STING signaling and propose CAD inhibition as a promising combinatorial strategy to enhance RT and RIT efficacy in CRC.